Developments on a 22 GHz microwave radiometer and reprocessing of 13-year time series for water vapour studies - A. Bell; A. Bell; E. Sauvageat; E. Sauvageat; E. Sauvageat; G. Stober; G. Stober; K. Hocke; K. Hocke; A. Murk; A. Murk (Atmospheric Measurement Techniques)
Long-term observations of water vapour in the middle atmosphere are important for climate studies and predictions, chemical and dynamical process studies, and modelling certain weather events with implications for surface conditions. Measurements from an instrument making middle-atmosphere water vapour observations near Bern, Switzerland – named MIAWARA (MIddle Atmosphere WAter vapour RAdiometer) – have been completely reprocessed since 2010. This has comprised of a new calibration which has been integrated into the framework for the calibration of other University of Bern radiometers and a new retrieval algorithm. The installation of a new spectrometer on the instrument has also allowed the comparison and correction of past observations. We present these corrected measurements and their subsequent analysis against data from Aura's Microwave Limb Sounder (MLS). The comparison shows that the corrected spectra yield more consistent values of water vapour mixing ratio between MIAWARA and Aura MLS, with a lower standard deviation of differences at all heights and a reduced bias between the two instruments at pressure (height) levels below (above) 0.3 hPa.